HIGH INFECTION OF Nilonema senticosum IN MATURE Arapaima gigas CULTIVATED IN THE PERUVIAN AMAZON - Mathews D., Patrick (2014)
Ten specimens of paiche Arapaima gigas from a semi-intensive fish farm located in the province of Maynas, Loreto, Peru were examined between June and October 2011 to identify the presence of parasitic helminths. This study identified a high infection of the nematode species Nilomena senticosum. The prevalence was 100% and a mean intensity of 80 parasites per fish.